Mobile-Based Learning Environment Development for Enhancing Reading Comprehension For 3rd Year Students in English Department, Champasak University, Laos - Luangsombath, Soulichanh; NOUTHAPHONE, Thiphachanh; PHALYCHANH, Bounmy; VONGPHACHANH, Somchith; VONGVILAY, Phoumchay (Souphanouvong University Journal Multidisciplinary Research and Development, 2025)
The rapid advancement of mobile technology has transformed educational methodologies, particularly in enhancing reading comprehension among students. This study aims to design and develop a mobile learning environment tailored for third-year English Department students at Champasack University. The objectives of study: 1) to construct an effective mobile-based learning environment; 2) to investigate self-directed learning ability; 3) to compare reading comprehension ability; 4) to assess learners' achievements in mobile-based settings; and 5) to explore students' opinions. Employing a mixed-methods research methodology, the study integrates document analysis, contextual studies, and theoretical framework synthesis, utilizing instruments such as surveys and evaluation forms to collect data from 25 students and 3 experts. Findings reveal that the mobile learning environment significantly enhances reading comprehension skills, with students demonstrating improved competencies in various reading strategies, including skimming and scanning. The evaluation of the mobile learning tool indicates positive perceptions among students, with a notable increase in learning effectiveness. However, areas such as previewing skills require further attention. Overall, the study underscores the potential of mobile learning to facilitate personalized and collaborative educational experiences, addressing existing challenges in reading proficiency and preparing students for a complex, information-rich world.